INCREASING THE COMPETITIVENESS OF GRADUATES USING THE INDEPENDENT LEARNING METHOD - INDEPENDENT CAMPUS THROUGH TECHNOLOGY EDUCATION - Debby Latifah Simatupang (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The aim of this research is to find out what factors arise from the results of previous research regarding increasing the competitiveness of graduates with the Independent Learning Campus (MBKM) program. The approach in this article uses a qualitative approach. Data was collected through the library research method. The results of this research are that programs to increase the competitiveness of college graduates can be realized by providing adequate infrastructure to meet these needs. The industrial factor in the MBKM policy is highlighted and strengthened by giving students the right to take programs and transfer credits at the end of the program